Synthesis, electrical and magnetotransport properties of polypyrrole-MWCNT nanocomposite - BLAU, WERNER; PADAMATI, RAMESH (My University, 2012)
The present work describes the preparation of nanocomposites in which the multiwall carbon nanotubes (MWCNT) have been mixed with conducting polypyrrole (PPy) via an in situ chemical oxidative preparation method. To reveal their structural, morphological and thermal properties, the composites have been characterized by X-ray diffraction, field emission scanning electron microscope, Fourier transform infrared, thermogravimetric analysis respectively. Electrical transport and magnetotransport properties have been investigated in the temperature range 77?300 K in presence as well as in absence of magnetic field up to 1Tesla. The conductivities of the composites are greater than that of pure polypyrrole. All the investigated samples follow Mott?s variable range hopping (VRH) theory whereas the magnetic field dependent conductivity have been explained in terms of two opposite but simultaneously acting hopping effect-wave function shrinkage and forward interference effect.
PUBLISHED
Keywords: Condensed matter physics; A. Polypyrrole; nanotubes; Nanoscience & Materials